KEY ASPECTS OF THE DEVELOPMENT AND ACHIEVEMENTS OF BASKETBALL IN SERBIA (Physical Culture and Sport: Scientific Perspective, 2025)
bian basketball is a key phenomenon in global sports, playing a significant role in the development of basketball on the international stage. With deep-rooted traditions, an effective system for training young players, and consistent success in international competitions, Serbia stands as one of the world's leading basketball nations. This article highlights various stages of the development of Serbian basketball, analyzes its current state, and explores prospects for the sport's further growth in the country.The nation consistently achieves high results in international competitions such as the World Championships, EuroBasket, and the Olympic Games. Studying the success of this national basketball system allows for the identification of key aspects contributing to its effectiveness and creates opportunities to adapt best practices in sports training for other countries. Specifically, by analyzing certain factors in the training of basketball players in Serbia and Ukraine, one can identify their strengths and weaknesses, which may serve as a foundation for developing new strategies for the national basketball team.Since the 1990s, Serbian basketball has faced certain challenges due to political and economic circumstances, but thanks to a strong sports structure, it has maintained its position. The successes of clubs like "Partizan" and "Crvena Zvezda" on the European stage have contributed to the further development of basketball in the country. Additionally, a significant number of Serbian players have begun building successful careers in the NBA and European leagues, further strengthening the authority of Serbian basketball.Among the most outstanding Serbian basketball players, names such as Vlade Divac, Peja Stojaković, Nemanja Bjelica, and Nikola Jokić stand out. Their contribution to the development of global basketball is invaluable. It is also worth mentioning renowned coaches such as Željko Obradović, who has won numerous EuroLeague titles with clubs like Partizan, Real Madrid, Panathinaikos, and Fenerbahçe. Svetislav Pešić led the Yugoslav national team to victory in the 2002 FIBA World Championship, won the EuroLeague with Barcelona in 2003, and coached the Serbian national team to a silver medal at the 2023 FIBA World Cup.
Keywords: history; basketball; achievements; Serbia; key aspects; Ukraine; international experience